Lung Transplantation as a way to Escape Pneumonia in Patients with COVID-19: Lessons from ARDS and Influenza - Reyhaneh Shams Khozani; Dorsa Shekouh; Sayyed Amirreza Hosseini; Mehrnush Saghab Torbati; Mahsa Noorian; Reyhaneh Rabiei; Qazal Mohseni; Hossein Rostami Rad; Shakiba Shaterzadeh Bojd; Parastoo Hosseini; Arina Ansari; Kimia Godazandeh; et al. (Interna Publishing, 2021)
In this era, the novel Coronavirus, referred to as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), a life-threatening virus with a high mortality rate (4.2%) and with no absolute treatment as of yet, may ultimately result in acute respiratory distress syndrome (ARDS). ARDS is one of the fatal complications, highlighted by pulmonary infiltration and severe hypoxemia. This condition can be developed from primary lung inflammation caused by various viruses, particularly influenza viruses, some of the most common human pathogens. Due to this issue, many studies explored several approaches for ARDS treatment. Lung transplantation has been claimed as an efficient cure for severe ARDS and Influenza, which can also be offered for treating critical lung complications of SARS-CoV-2. Thereupon, to the best of our knowledge for the first time, we aimed to review all available data about capability of lung transplantation for the treatment of critically ill patients with ARDS, Influenza, and SARS-CoV-2.